Efektivitas Pengelolaan Objek Wisata Keraton Kasepuhan Oleh Badan Pengelola Keraton Kasepuhan Dalam Pengembangan Pariwisata Di Kota Cirebon - Murod, Muhammad Fakhri; Stiawati, Titi; Cadith, Juliannes (Department of Public Administration, Parahyangan Catholic University, 2024)
This study aims to determine and measure the effectiveness of the management of the Kasepuhan Palace tourist attraction by the Badan Pengelola Keraton Kasepuhan in tourism development in the city of Cirebon with the theory used, namely the effectiveness approach by Hari Lubis & Martani Huseini (2009: 111-118) which includes; Source Approach, Process Approach, and Target Approach. The research method used is qualitative through a descriptive approach. In determining research informants using purposive techniques, namely selected with certain considerations and objectives that understand the focus of the research. The data collection techniques used in this research are interviews, observations, and documentation studies. The results of this study, among others, the quality of human resources owned has not been competent due to the absence of educational standards in the recruitment system, the absence of work mechanisms contained in the Standard Operating Procedures, weak preservation efforts of historical heritage objects and cultural heritage objects caused by budget constraints, maintenance mechanisms that are still traditional, and procedural reporting of repairs that are not easy, weak communication and coordination between the Dinas Kebudayaan dan Pariwisata Kota Cirebon and the Badan Pengelola Keraton Kasepuhan on the focus of tourism issues, and managers do not have a commitment to the strategic planning of tourist attraction development. The conclusion of this research is that the management of the Kasepuhan Palace tourist attraction carried out by the Badan Pengelola Keraton Kasepuhan has not been effective.